Real‐time optical spectroscopic monitoring of nonirrigated lesion progression within atrial and ventricular tissues. Issue 4 (26th December 2018) - Singh‐Moon, Rajinder P.; Yao, Xinwen; Iyer, Vivek; Marboe, Charles; Whang, William; Hendon, Christine P.
Abstract : Despite considerable advances in guidance of radiofrequency ablation (RFA) therapy for the treatment of cardiac arrhythmias, success rates have been hampered by a lack of tools for precise intraoperative evaluation of lesion extent. Near‐infrared spectroscopic (NIRS) techniques are sensitive to tissue structural and biomolecular properties, characteristics that are directly altered by radiofrequency (RF) treatment. In this work, a combined NIRS‐RFA catheter is developed for real‐time monitoring of tissue reflectance during RF energy delivery. An algorithm is proposed for processing NIR spectra to approximate nonirrigated lesion depth in both atrial and ventricular tissues. The probe optical geometry was designed to bias measurement influence toward absorption enabling enhanced sensitivity to changes in tissue composition. A set of parameters termed "lesion optical indices" are defined encapsulating spectral differences between ablated and unablated tissue. Utilizing these features, a model for real‐time tissue spectra classification and lesion size estimation is presented. Experimental validation conducted within freshly excised porcine cardiac specimens showed strong concordance between algorithm estimates and post‐hoc tissue assessment. Abstract : Success rates of radiofrequency ablation treatment of cardiac arrhythmias suffer in part due to lack of tools for precise intraoperative evaluation of lesion delivery. In this work, an algorithm is proposed for real‐time processing of near‐infrared reflectance spectra including lesion classification and approximation of lesion depth in both atrial and ventricular tissues. Experimental validation conducted within excised porcine cardiac specimens showed strong concordance between algorithm estimates and post‐hoc tissue assessment.